The prevalence of myopia among school-going children (6-14 years) in Chidambaram, Tamil Nadu: a cross-sectional study - Dhivyaa, T.; Kalyani, P.; Felix, A. John William (International Journal Of Community Medicine And Public Health, 2021)
Background: Refractive errors are one of the most common causes of visual impairment worldwide. Uncorrected, under corrected and undetected refractive errors among school-going children are the most significant problem in developing countries like India. Schools are the best place for early detection of ocular morbidity. Myopia, hypermetropia and astigmatism are the three main types of refractive errors, of which myopia is the most common type in school-going children. Methods: This descriptive cross-sectional study was carried out for the period of 6 months from October 2019 to March 2020 among school-going children in the field practice area of Chidambaram. 575 students from two government and 2 private schools were selected conveniently. Data were collected using a pre-tested, semi-structured questionnaire and analysed using Statistical Package for social sciences (SPSS) software version 23. Descriptive statistics were used and a Chi-square test of significance was applied. Results: The prevalence of myopia was found to be 12.9%. There is a significant association between the frequency of reading hours, time spent on outdoor activities and mobile usage and the presence of myopia (p<0.05). Conclusions: The risk factors like hours of reading books, time spent on outdoor activities and mobile usage are the contributing factors for the development of refractive error like myopia. They are easily detectable through the program on eye screening of school children.